EDUCACIÓN, REORGANIZACIÓN DEL TRABAJO, TERRITORIALIDAD Y FORMACIÓN DOCENTE - Vallejo Osorio, León (Cuadernos de Administración, 2006)
The present cycle of accumulation, that within these decades governs the capitalist economies, has introduced -as an essential device that rearranges the set of the social practice- mechanisms that guarantee the reproduction of the social formation as a capitalist society. In this text, two concrete forms of these mechanisms are discussed and analysed: one of them that plays for its total legitimation, is the intermediation, that has turned into a sponge that catches extraordinary gains by the way of rent, supported by the State. The other axis -mechanism- that defines the caracter of which could be the present public policies, is born and powered in the reorganisation of work. In the dinamic that takes to the fact that more and more sectors of the social practice arer discovered as potentials or real “productive works”, producers of capital gain and/or rental. Thus it is maintained and argued in this document: first, that the path that unites this two mechanisms has turned around the handling that has been given to the so called “successive generations” of the processes and to the conception itself of the “control of the quality”. Secondly, that the last “generation” discovered that the “society of knowledge” needs and must generate and individual (worker-consumer) “entrepreneur of himself”. These are the avenues of the “free lance” and the controls that imposd the principles of the “Strategic Management”. Third, that this demands, the “reconversion”, the reengineering of the citizens, in order to transform them into neo-classic subjects, in beings that realise in practice as clients in sine of the -now omnipresent supermarket. Subjects that know how to “do in context”. The implications in the previous afirmations are immediate: it´s no long only about accepting that the work force is merchandise, but also, we must understand that the qualification of the work force is too, and in an essential way. Thats why there’s the necessity of companies that are dedicated to this business. This generates a whole teaching and the devices of the public policies that affects and determines the conditions and characters of the school practice. The maqterial conditions from where take place praxis and the results of the task of teachers, students and, with them, of the society as a whole.